2018
DOI: 10.1002/jcp.26835
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic profiling identifies novel molecular targets of pterostilbene against experimental diabetes

Abstract: Pterostilbene (PTS), a naturally occurring stilbene, confers protection against oxidative and cytokine stress induced pancreatic β-cell apoptosis in vitro and in vivo. To provide insights into the molecular mechanism, we performed a proteomic study on the pancreas of PTS-treated diabetic mice using electrospray ionization tandem-mass spectrometry (LC-MS/MS). A total of 1,260 proteins were detected in triplicate samples. Of which, 359 proteins were found to be differentially regulated in streptozotocin-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Our earlier studies confirmed that pterostilbene, an Nrf2 activator, conferred protection against oxidative stress by elevating the levels of Nrf2 and its downstream genes and against cytokine stress [22,24]. Further, the proteomic profiling of pancreatic tissue isolated from pterostilbene treated mice demonstrated that the majority of differentially regulated proteins were associated with oxidative and ER stress pathways [61].…”
Section: Discussionsupporting
confidence: 69%
“…Our earlier studies confirmed that pterostilbene, an Nrf2 activator, conferred protection against oxidative stress by elevating the levels of Nrf2 and its downstream genes and against cytokine stress [22,24]. Further, the proteomic profiling of pancreatic tissue isolated from pterostilbene treated mice demonstrated that the majority of differentially regulated proteins were associated with oxidative and ER stress pathways [61].…”
Section: Discussionsupporting
confidence: 69%
“…Our findings indicated that the administration of PTS normalized the levels of 315 proteins that were modulated in diabetic mice. Outstandingly, a major proportion of these proteins were involved in the regulation of redox imbalance, the antioxidative stress response, the unfolded protein response, and ER degradation pathways, indicating that PTS treatment plays a crucial role in the rehabilitation of defective metabolic processes and stress sensors in diabetes [ 101 ].…”
Section: Therapeutic Properties Of Ptsmentioning
confidence: 99%
“…An imbalance of insulin generation or dysfunction of insulinproducing pancreatic β-cells leads to type 1 diabetes (T1D), 135 which plays a key role in the progression of CD. 117 It has been reported that OS is implicated in the progression of diabetes.…”
Section: Diabetesmentioning
confidence: 99%
“…An imbalance of insulin generation or dysfunction of insulin-producing pancreatic β-cells leads to type 1 diabetes (T1D), which plays a key role in the progression of CD . It has been reported that OS is implicated in the progression of diabetes. , An excess of blood glucose can also lead to protein glycation and the oxidation of bound glucose and thus, to the generation of AGEs, which are directly correlated with type 2 diabetes .…”
Section: Oxidative-stress-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation